Pengembangan Modul Pembelajaran IPA Pada Siswa Kelas VIII SMP Urumb Merauke - Evy Nurvitasari; Diah Harmawati (Universitas Musamus, Merauke, Papua, 2020)
The purpose of making modules is to determine the level of convenience when used by students. Research conducted at Urumb Middle School has been carried out well, while the Natural Sciences module has been tested on students. The research method is the ADDIE R&D model which includes analysis, design, development, implementation, and evaluation. Evaluation is the final stage to make improvements after receiving advice and comments from material experts, teachers and students. The results of the study showed that the material expert validation was 92.5%, the teacher validation was 93.7%, and the student validation was 88.8% so that it was categorized as very valid and suitable for use